2016
DOI: 10.1111/cico.12181
|View full text |Cite
|
Sign up to set email alerts
|

The Global City versus the City of Neighborhoods: Spatial Practice, Cognitive Maps, and the Aesthetics of Urban Conflict

Abstract: Political‐economy, which conceptualizes space as a resource over which different groups struggle, has long been the dominant perspective in the study of urban conflict. However space is also a cultural object from which actors derive particular meanings. In order to understand how meaningful interpretations of space give rise to urban conflict, this paper examines the architectural expansions of two Toronto museums. Both projects were fiercely opposed by local creative and professional class residents—a group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…In line with Theodore Schatzki (), a practice is understood as a nexus of doings and sayings that brings the individuals involved “into contact with objects, people, and events” (Patterson :168) in their everyday lives. A practice can be studied both by directing the attention to the performative carrying out of its activities through the individuals involved and by focusing on its constitutive organizing elements, where a distinction is made between specific understandings (how to do or say something), implicit or explicit rules, as well as specific leitmotifs in which human actors engage according to the situation and, in particular, to societal contexts (Schatzki ).…”
Section: Central Aspects Of a Praxeological Research Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…In line with Theodore Schatzki (), a practice is understood as a nexus of doings and sayings that brings the individuals involved “into contact with objects, people, and events” (Patterson :168) in their everyday lives. A practice can be studied both by directing the attention to the performative carrying out of its activities through the individuals involved and by focusing on its constitutive organizing elements, where a distinction is made between specific understandings (how to do or say something), implicit or explicit rules, as well as specific leitmotifs in which human actors engage according to the situation and, in particular, to societal contexts (Schatzki ).…”
Section: Central Aspects Of a Praxeological Research Perspectivementioning
confidence: 99%
“…Certificates were presented, a message from the state government was read out, and the local music association provided musical accompaniment (ibid.). Last, but not least, “the seven fire brigades demonstrated numerous fire–fighting exercises” (NÖN 39/2005:16). Everyone involved had done their work.…”
Section: Reception and Planning Practices Of Roundabout Art And Its Smentioning
confidence: 99%
“…While important, these issues have tended to overshadow the characteristic that makes culture-led developments “cultural” in the first place: They serve as symbols that communicate meanings about place and identity. Growing evidence suggests, however, that cultural meanings have a significant impact on both the political (McGovern 2009; Miller and Silver 2015; Patterson 2016) and economic (Silver and Clark 2016; Silver and Miller 2013) characteristics of cities and neighborhoods. Thus, it is not only important that the cultural sector as a whole has gained prominence within urbanization; it is also important to account for particular types of culture-led development, the variable meanings they express, and the implications of those meanings for life in the city.…”
Section: The Cultural Citymentioning
confidence: 99%
“…Similarly, Patterson (2016) demonstrated that the developers of two iconic projects in Toronto exhibited a more cosmopolitan sense of place than local residents, which led to conflict over how the projects should be designed in relation to their surrounding context.…”
Section: Iconic Architecturementioning
confidence: 99%
“…Trying to describe the specificity of the former, Harvey (1996) indicated that a common phenomenon is the closing up of the people living in one area in order to prevent the invasion of socially unaccepted groups. If we add the activity of city authorities and city visitors, the participation of developers and other external entities in the city, it turns out that there are many exogenous factors causing social tensions in neighbourhood societies (Clark, Kearns et al 2016;Patterson 2016). When we complete this picture of potential tensions in neighbourhoods with internal differences -ethnic (Glikman, Semyonov 2012;Hanhörster, Weck 2016), social (Wu, Feng Hou et al 2011) and economic (Owens 2012), potential conflicts become practically inevitable (Buitrago 2013).…”
Section: Social Attitudes Towards Place-making On the Neighbourhood Lmentioning
confidence: 99%